Extracellular vesicles: A dive into their role in the tumor microenvironment and cancer progression - Lopez, Kassandra; Lai, Seigmund Wai Tsuen; Lopez Gonzalez, Edwin De Jesus; Dávila, Raúl G.; Shuck, Sarah C. (Frontiers in Cell and Developmental Biology, 2023)
Extracellular vesicles (EVs) encompass a diverse set of membrane-derived particles released from cells and are found in numerous biological matrices and the extracellular space. Specific classes of EVs include apoptotic bodies, exosomes, and microvesicles, which vary in their size, origin, membrane protein expression, and interior cargo. EVs provide a mechanism for shuttling cargo between cells, which can influence cell physiology by transporting proteins, DNA, and RNA. EVs are an abundant component of the tumor microenvironment (TME) and are proposed to drive tumor growth and progression by communicating between fibroblasts, macrophages, and tumor cells in the TME. The cargo, source, and type of EV influences the pro- or anti-tumoral role of these molecules. Therefore, robust EV isolation and characterization techniques are required to ensure accurate characterization of their association with disease. Here, we summarize different EV subclasses, methods for EV isolation and characterization, and a selection of current clinical trials studying EVs. We also review key studies exploring the role and impact of EVs in the TME, including how EVs mediate intercellular communication, drive cancer progression, and remodel the TME.